KEKERASAN BERBASIS GENDER ONLINE (KBGO) DALAM KONTEKS MISOGINI DAN SEKSISME PADA MEDIA SOSIAL X (TWITTER) - Rani, Cantika; Destiana, Nida; Angelie, Dheavica (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
This study aims to determine how online gender-based violence (OBGV) occurs in the context of misogyny in the @gilbertkurnia1 account on social media X (Twitter). Using a descriptive qualitative research method using a virtual ethnography approach, this research seeks to present a description of the forms of communication included in the category of online gender-based violence (GBV) as a phenomenon of violence that is the object of this study. The data in this study were obtained using two methods, namely by observing the @gilbertkurnia1 Twitter account within the period of October 31 - December 06 2024 and using literature review that is relevant with the research topic to support the discussion in this study. The results of this study show that the content of tweets, retweets/reposts, replies, and quote tweets uploaded by the @gilbertkurnia1 account on X (Twitter) is content with topics of misogyny, gender violence, the use of sexist terms, hatred towards feminists, and the relationship of religion values toward gender context. The interactions carried out by @gilbertkurnia1 account through the tweets, replies, retweets or reposts, and quote tweet features on social media X (Twitter) can be analyzed as online gender-based violence (KBGO) in the context of misogyny, sexism, and objectification which are closely related to patriarchal culture. In his posts, @gilbertkurnia1 carries narratives that demean women such as the words “baby incubator”, “baby printer”, and “child printing vending machine”, as well as narratives that reflect hatred towards feminists such as the phrases “Feminist = bitch/slut”, “Feminist = loser”, and “Feminist = a single hole for everyone.”